2016
DOI: 10.1111/jpi.12367
|View full text |Cite
|
Sign up to set email alerts
|

Identification, transcriptional and functional analysis of heat‐shock protein 90s in banana (Musa acuminata L.) highlight their novel role in melatonin‐mediated plant response to Fusarium wilt

Abstract: As one popular fresh fruit, banana (Musa acuminata) is cultivated in the world's subtropical and tropical areas. In recent years, pathogen Fusarium oxysporum f. sp. cubense (Foc) has been widely and rapidly spread to banana cultivated areas, causing substantial yield loss. However, the molecular mechanism of banana response to Foc remains unclear, and functional identification of disease-related genes is also very limited. In this study, nine 90 kDa heat-shock proteins (HSP90s) were genomewide identified. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(64 citation statements)
references
References 71 publications
(242 reference statements)
2
62
0
Order By: Relevance
“…Plant melatonin level was extracted from leave samples using extraction mixture (acetone:methanol:water (v:v:v) = 89:10:1). After centrifugation, the endogenous melatonin was quantified in the supernatant using melatonin enzyme‐linked immunosorbent assay (ELISA) kit (Jianglai Biotechnology, Shanghai, China) as Wei et al described …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant melatonin level was extracted from leave samples using extraction mixture (acetone:methanol:water (v:v:v) = 89:10:1). After centrifugation, the endogenous melatonin was quantified in the supernatant using melatonin enzyme‐linked immunosorbent assay (ELISA) kit (Jianglai Biotechnology, Shanghai, China) as Wei et al described …”
Section: Methodsmentioning
confidence: 99%
“…In recent years, accumulated evidence has confirmed that melatonin ( N ‐acetyl‐5‐methoxytryptamine) is involved in plant against various pathogen bacterials and fungers, including Diplocarpon mali , Fusarium oxysporum f. sp. cubense , and Pseudomonas syringe pv. tomato DC3000 .…”
Section: Introductionmentioning
confidence: 99%
“…Since the first discovery of melatonin in plants in 1995, many pharmacological studies have been performed to investigate its functional and physiological significance . Large numbers of experiments involving exogenous application of melatonin to a series of plant species indicated that melatonin acts as a biostimulator in plants by enhancing a myriad of defense responses against abiotic stresses, including oxidative stress, high temperature, cold, senescence, drought, and salt, as well as biotic stress such as pathogen attacks . In addition to the defense responses, melatonin has also been implicated in promoting plant growth processes, such as seedling growth, flowering, nutrient absorption, and fruit ripening, suggesting a potential role of melatonin as a plant growth factor .…”
Section: Introductionmentioning
confidence: 99%
“…Positively, functions of melatonin include regulation of circadian rhythms, immunomodulation, and scavenging free radicals . In plant, melatonin protects plants against pathogen attack mainly by regulating plant innate immunity to trigger the defense responses . For the application of exogenous melatonin on Arabidopsis thaliana and Malus prunifolia leaves, various defense genes contributing to resistance to pathogen are induced by exogenous melatonin .…”
Section: Introductionmentioning
confidence: 99%